Most Recent Data (2003). Statistics Canada. CANSIM: Business Performance and Ownership - Small and Medium-Sized Businesses | Country: Canada | Province: Newfoundland and Labrador | Table: Survey of innovation, selected service industries, percentage of business units whose operations were part of a larger firm | Variable: Operations part of a larger firm with sole purpose to provide services to other units in firm, Engineering servicesá, All business units | Units: %, 2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-023. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Business Performance and Ownership - Small and Medium-Sized Businesses | Country: Canada | Province: Newfoundland and Labrador | Table: Survey of innovation, selected service industries, percentage of business units whose operations were part of a larger firm | Variable: Operations part of a larger firm with sole purpose to provide services to other units in firm, Engineering servicesá, All business units | Units: %, 2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-023. Dataset: Provides statistics on characteristics and financing activities of small and medium-sized businesses in Canada, including balance sheets and investment activities, sources of financing, credit amounts authorized, credit amounts outstanding, and types of financing instruments, and other measures of the economic importance of small firms. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Small Businesses, Financials